TRADISI NUJUH BULANAN MASYARAKAT JAWA DI DESA SIALANG BARU KECAMATAN KABUPATEN SIAK - Siti Muniroh; T Romy Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tradition Nujuh Bulanan is a custom or a ceremony conducted in the 7th time a woman's first pregnancy. Nujuh Bulanan events are often held by some people who have tribes Java because it is a tradition handed down by ancestors past. Nujuh Bulanan event in the village of beehive New District of Lubuk In Siak in implementation has no longer the same as in past, but at the present time has been the change in both the ordinance and the meaning contained in that tradition. This study aims to find out about the changes that occur in the nujuh bulanan tradition in the village of beehive New District of depths in Siak district. The type of data obtained in this study used descriptive qualitative method. Techniques used the data collected through observation and interviews. Inforaman gained as many as 7 people: one person's status as the host of the nujuh bulanan and 6 people from the community who had had monthly nujuh event. Data collection techniques using purposive technique. After the interviews, observation, and documentation. Results of research conducted in general, the authors can show that in the tradition of nujuh bulanan has experienced a change in the procedure during the first implementation that has seven steps being taken, while at the present time are made only 6 stages. Changes in this nujuh bulanan tradition that is because of the factor of family, tolerance, the absence of sanctions and technology. So by increasing the advance of age at the present time the above factors are influencing the course of events this nujuh bulanan.Keywords: Tradition of Nujuh Bulanan, and Changes